Pocketbook of clinical IR a concise guide to interventional radiology - Warhadpande, Shantanu; Lionberg, Alex; Cooper, Kyle (Kyle James) (Thieme, 2019)
Excel at clinical IR with insightful perspectives from both current residents and senior interventionalists! Interventional radiology training has evolved rapidly during the last decade, with recent recognition as a primary medical specialty by the American Board of Medical Specialties. The number of IR residency positions continues to increase each year with a greater number of trainees rotating through the IR elective. The bar is set high and expectations of trainees have increased. Written clearly, concisely, and at a trainee's level, Pocketbook of Clinical IR: A Concise Guide to Interventi.